Fortolkning, betydning og magt: Reklamestereotyper til forhandling - Rudloff, Maja (K&K - Kultur og Klasse, 2022)
Advertising images have been a focal point of feminist activism and protest since the 1960s, and criticism of the negative impact of commercially mediated gender stereotypes has also been met with political attention. As an EU member state, Denmark is obliged to integrate the objectives of eliminating the media’s stereotypical representations of gender into their respective national legislation and guidelines. Nevertheless, a review of the Danish Consumer Ombudsman’s (FO) and the Radio and TV Board’s (RTN) practices, which are the two Danish bodies that regulate advertising in Denmark, demonstrates a reluctance in prohibiting the dissemination of advertising that may be perceived as offensive or sexist. Through analysis of advertising examples that have been accused of gender discrimination, and their case processing by the two above-mentioned authorities, the article here focuses on advertising as an arena for different and often conflicting agendas and discourses. The article revolves around the importance of advertising images’ representations of gender as well as their regulation and politicization and it demonstrates how visual messages and their significance for equality are up for constant debate. By questioning the way in which Danish authorities evaluate gender discrimination in advertising it thus enters a broader international and political discussion about the formative power of commercial images.